Ontological Difference in Martin Heidegger - Ridruejo Alonso, Pedro (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The first approach to the topic deals with the implications of a philosophical theory of difference and of the ontological voice’s trajectory. The second approach relates the stages of Heidegger’s thought and considers the special relevance that each stage has in the evolution of his work. The unfolding of the topic begins, for Heidegger, with a review of the four previously formulated theses on Being. The review reveals the author’s position in relation to each of the texts dealing with ontological difference, from its traces in Sein und Zeit up to Identität und Differenz. The article then looks for a systematic manner to approach ontological difference. Finally, with special emphasis on the work of Derrida, the article discusses the traditional criticisms of scholastic philosophy and those of Nietzsche and his commentators.